MINDFUL LEARNING STRATEGIES IN SUPPORTING THE MENTAL WELL-BEING OF SLOW LEARNERS IN ELEMENTARY SCHOOL - icha zuliana rahma putri; Minsih (SOSIOEDUKASI, 2026)
Mindful learning strategies act as a relevant learning approach for slow learners who need a calmer, more conscious and focused learning approach to support their mental well-being. This research was conducted with the aim of analyzing the application of mindful learning  strategies in supporting the mental well-being of slow learner  students and identifying supporting and inhibiting factors for its implementation. This research strengthens learning theories that prioritize psychological health as a foundation for slow learners. This research is a qualitative research with a case study design. Research data was obtained through observation of learning activities, interviews with classroom teachers and tutors, and documentation of the learning process in the classroom. The validity of the data in this study is through source triangulation and technique triangulation. The data analysis technique is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study showed that (1) mindful learning was applied through: simple breathing exercises, teaching that focused on one activity in full, self-reflection after learning; (2) Factors supporting implementation include teacher support, classroom atmosphere, suitability of learning methods, and support from schools, while inhibiting factors include time constraints, variations in students' abilities, and unstable environmental atmosphere